HRCT FEATURES OF COVID-19 IN RELATION TO DURATION OF DISEASE - Shah, Sajida; Malik, Zainab; Shah, Inamullah; Babar, Sadia; Ahmad, Farhad; Naveed, Arsalla (Journal of Ayub Medical College Abbottabad, 2021)
Background: Despite the fact that much has been written on various aspects of COVID-19, literature lacks a detailed and accurate description of HRCT findings in relation to the duration of the disease. The aim of this study was to investigate the difference in HRCT scan findings depending on the time after onset of the disease. The objective of the study is to identify and compare findings of HRCT scan at different time points after onset of the disease. Methods: A total of 224 patients, scanned over a period of 2 months, were placed in one of the four groups at the time of their scan depending on the days lapsed after their symptoms appeared. All scans were carried out on the same machine. Findings in each group were recorded and compared. A finding showing significant difference between groups indicates its importance in describing the course of the disease. Analysis was done on SPSS 23. Results: Ground glass opacities in posterior segments of one or more lobes was the most common feature and had a significant association with first 5 days of the disease (p=.027). Interlobular thickening and subpleural reticulation, are found between 3-5 days or later in the course of the disease (p=.000). Conclusion: Ground glass opacities located in posterior segments are the predominant feature in patients who are scanned up to 5 days after their symptoms appear. This feature is the most common in scans done in asymptomatic cases too. Interlobular septal thickening and subpleural reticulation start appearing at 3 days of disease process.